Investing in sustainability: economic models and sustainable finance products. - Raja, Rehan; Adam Sa'ad, Auwal; Hina, Fatima; Liaqa, Ali (Springer, 2025)
The world is facing several mounting challenge of climate alteration, resource depletion, social inequalities, biodiversity losses, etc. That enhance the importance of sustainability and become a core concern for businesses and investors.